Influence of YouTube as a Supplementary Learning Tool in Higher Education - Olivo, Michael C. (International Journal of Computing Sciences Research; Vol 9 (2025): Volume 9, 2025)
Purpose -  This study aims to evaluate YouTube's influence as an educational resource in higher education and examine its benefits and drawbacks for students. Method – To evaluate YouTube’s impact as a learning tool, a descriptive research design was utilized to systematically and accurately gather information. A developed and validated survey questionnaire was used in a probability sampling for this study. Results –  YouTube's platform gained an overall average score of 4.07, suggesting that it is considered a highly effective learning resource. It is also perceived as a beneficial tool in learning, as it gained a high average score of 4.58 for its advantages over traditional textbooks and magazines. Conclusion –  YouTube proves to be an exceptionally effective supplementary learning tool used in higher education. It proves invaluable assistance during urgent academic challenges and facilitates a deeper understanding of complex topics in just a few clicks. Recommendations –  Despite the diversity in learning styles, optimizing the use of a learning tool requires adapting and varying learning routines and approaches. It is highly recommended to incorporate digital platforms such as YouTube to enhance student performance. University Professors, particularly in computer science courses, should design programs that encourage students to explore and effectively utilize these digital resources, leveraging them to their advantage throughout their academic journey. Research Implications –  This study aims to advocate for the integration of digital platforms to enhance learning outcomes. Practical Implications –  This study shows that the integration of digital platforms that are normally used by the current generation can enhance their education and academic strategies. Social Implications –  This research demonstrates that YouTube offers more than just entertainment; it can also significantly enhance the educational experience. It provides a valuable tool for both professors and students to create more interactive and engaging classes, maximizing the platform’s benefits for academic advancement.